Management of febrile neutropenia: A description of clinical and microbiological findings by focusing on risk factors and pitfalls - Fatemeh Karimi; Farzaneh Ashrafi; Azadeh Moghaddas; Ali Derakhshandeh (Wolters Kluwer Medknow Publications, 2018)
Objective: Febrile neutropenia (FN) is one of the most serious clinical problems in patients with hematologic malignancies and patients receiving chemotherapy. The present study was implemented to determine precisely how FN is managed in most referral hospitals in Isfahan (Iran) and what are the characteristics of FN patients as well as risk factors associated with FN development. Methods: This study was a cross-sectional study performed over a period of 6 months on patients hospitalized in the Hematology-Oncology Center of Omid Hospital, Isfahan, Iran. The information was collected by filling the designed data abstraction form. Findings: A total of 115 oncology patients were admitted with or encountered to FN. This equates to a cumulative incidence of 1.26% of FN cases per 1000 oncology admissions. The average age was 49.5 ± 18.02 years (range 18-85 years), with 42.6% of patients being female. The most frequently prescribed antibiotic agents were meropenem (91.3%) and vancomycin (47.82%) alone or in combination. Empiric antifungal agents initiated in 20.86% of cases, and we could not find any patients who needed to receive antiviral treatment. From all positive cultures, Gram-positive microorganisms were the most found pathogen. Among them, female sex (42.6%) and lymphopenia (26.5%) were the most noted predictors. Neutropenia (81.7%) was the most reported risk factors for serious complications. Conclusion: Although our center is university-affiliated, there are still several points, and pitfalls must be considered and revised in the management of FN patients. Obtaining and assessing the samples microbiologically and antibiotic therapy accordingly were the most troublesome complications.